2000
DOI: 10.1055/s-2000-6287
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Coupling of Aryl Sulfonates with sp2-Hybridized Nitrogen Nucleophiles: Palladium- and Nickel-catalyzed Synthesis of N-Aryl Sulfoximines

Abstract: Several sulfoximines have been arylated in good to high yield by palladium catalysis using aryl nonaflates and aryl triflates. Moreover, the successful synthesis of N-aryl sulfoximines from aryl tosylates is described using a Ni(COD) 2 /BINAP catalyst.Palladium-catalyzed processes which employ aryl or vinyl sulfonates 1 are becoming increasingly attractive, because they are easily accessible from the corresponding phenols and ketones, respectively, thus allowing an entirely different class of substrates -other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
55
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(55 citation statements)
references
References 5 publications
0
55
0
Order By: Relevance
“…Bolm provided the example for the amination of aryl tosylates with sulfoximines by employing BINAP as ligand for Ni(0) [5]. Fort developed the Ni(II)eNaHebipyridine [6e9] and Ni(II)eNaHeNHC [10] systems as efficient catalysts for the couplings of aryl and heteroaryl chlorides with various nitrogencontaining substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Bolm provided the example for the amination of aryl tosylates with sulfoximines by employing BINAP as ligand for Ni(0) [5]. Fort developed the Ni(II)eNaHebipyridine [6e9] and Ni(II)eNaHeNHC [10] systems as efficient catalysts for the couplings of aryl and heteroaryl chlorides with various nitrogencontaining substrates.…”
Section: Introductionmentioning
confidence: 99%
“…In 2000, Bolm and coworkers, while studying the palladium‐catalyzed arylation of sulfoximines with aryl triflates and nonaflates, found that a Ni(cod) 2 /BINAP catalyst mediated the coupling of aryl tosylates with sulfoximine (two examples only), whereas palladium did not (Scheme ) 61…”
Section: Arylation Of Nh Nucleophiles Other Than Aminesmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] However, the cost of reagents, removal of trace palladium from late stage synthetic intermediate, and difficulties in coupling of electron-rich or ortho-substituted aryl halides are the major drawbacks of this method. In addition to palladium catalysts, rhodium, [13][14][15][16] and nickel [17][18][19][20] transition metal catalysts have been developed for N-arylation of aryl halides with amines, however, these methods have drawbacks in terms of atom economy, since they generate large amounts of solid waste and also require a stoichiometric amount of base. Copper mediated N-arylation is another choice of reaction for the production of these compounds due to cheap price and environmental friendly nature.…”
Section: Introductionmentioning
confidence: 99%